Dari absolutisme menuju dialog: Transformasi pedagogis etika Kristen dalam konteks postmodernitas dan multikulturalisme - Daniel Sudibyo Tjandra (KURIOS, 2025)
This article examines the pedagogical transformation in Christian ethics education that occurred due to the paradigm shift from absolutism to a dialogical approach in the context of postmodernity and multiculturalism. This study uses a critical analysis method of contemporary educational theology literature and case studies of pedagogical implementation in various Christian educational institutions. The findings indicate that this pedagogical transformation necessitates an epistemological reconstruction that does not compromise theological authority but instead opens up space for critical engagement with a plurality of perspectives. The practical implication is the development of a more inclusive, contextual, and dialogical pedagogical model in Christian ethics education.   Abstrak Artikel ini mengkaji transformasi pedagogis dalam pendidikan etika Kristen yang terjadi akibat pergeseran paradigma dari absolutisme menuju pendekatan dialogis dalam konteks postmodernitas dan multikulturalisme. Penelitian ini menggunakan metode analisis kritis terhadap literatur teologi pendidikan kontemporer dan studi kasus implementasi pedagogis di berbagai institusi pendidikan Kristen. Temuan menunjukkan bahwa transformasi pedagogis ini memerlukan rekonstruksi epistemologis yang tidak mengorbankan otoritas teologis namun membuka ruang untuk keterlibatan kritis dengan perspektif pluralitas. Implikasi praktisnya adalah pengembangan model pedagogi yang lebih inklusif, kontekstual, dan dialogis dalam pendidikan etika Kristen.